Time, time-frequency and displacement-frequency analysis of embolic signals - Leiria, A. (2015)
The characteristics of a new method, the displacement-frequency representation, prompted the study of its use for the analysis of embolic blood flow signals. This paper reports the comparison of displacement-frequency and time-frequency methods with time domain methods, in the characterization of emboli. The study was performed on clinical signals derived from gaseous and particulate embolic events. The results obtained with the different approaches were compared. The conclusions of this study provide encouragement for the use of displacement-frequency domain processing for this kind of analysis.